(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
Abstract: The research aims to determine the variation in the levels of the drought coefficient in Tripoli region, depending on the climatic data of Tripoli airport station, and on the two elements of temperature and rainfall, and using the Demarton formula to calculate the drought coefficient through its classification of climatic and vegetation regions, based on a period of 60 years, which was divided into two periods. The first period (1962-1991), and the second period (1992-2021). The general trend was also determined based on the simple folding regression equation, where the results showed that the values of (b) are positive, which proves that the second period was higher than the first period in average temperature, while the value of (b) was negative in precipitation rates, which indicates a decrease in its rate during the second period compared to the first period. As for the general trend of the drought coefficient, it varied between positive and negative in the values of (b) according to the variation of the seasonal climatic characteristics. The data was also subjected to testing the two periods based on the SPSS statistical program and using the Independent Samples T Test. The results of the data indicated that there was a slight variation in temperature between the two study periods at a level of statistical significance less than 5%, and that the drought coefficient did not witness a variation in the average unless there is a clear variation in temperature and rainfall and it is statistically significant.